I'm Here; I'm Queer: How One Parent Advocates for the Inclusion of Queer Youth. (March 2022) - Colvin, Kody; Edwards, Sean; Eng, Britnee
Educators and school administration are tasked with creating schools that support and affirm LGBTQ+ (lesbian, gay, bisexual, transgender, and queer) students and families. This study explores a high school in a conservative community as one parent attempts to advocate for their transgender child and other LGBTQ+-identifying students. Although school employees are mandated by state and federal laws to ensure that all students are free from bullying and harassment, the research highlights that schools remain hostile for many LGBTQ+ students. This article provides reflection questions throughout the case as a way for school leadership to grapple with and challenge their thinking regarding LGBTQ+-affirming strategies in their schools.